معوقات رقمنة الرابطة الولائية للرياضة المدرسية بولاية الواديــ دراسة ميدانية - عاد حمزة (My University, 2024)
ملخص الدراسة : هدفت الدراسة الى التعرف على أهم معوقات التحول الرقمى بالرابطة الولائية للرياضة المدرسية بولاية الوادي، ومن أجل ذلك وظفنا المنهج الوصفي التحليلي لملائمته لطبيعة الموضوع، وظف الطالب استمارة استبيانيه وزعت على عينة من 40 مسير بالرابطة، عولجت البيانات احصائيا بواسطة برنامج spss22، توصلنا الى أنه توجد معوقات بشرية ومعوقات تنظيمية وإدارية بدرجة كبيرة، في حين توجد معوقات مادية وتقنية بدرجة متوسطة، كما لا توجد فروق دالة إحصائية في رؤية أعضاء الرابطة لهاته المعوقات تعزى لمتغيرات الخبرة المهنية، المؤهل العلمي.وعليه أوصينا بضرورة الاهتمام بتوظيف المورد البشري الكفء في تسيير الرابطات وتوفير الموارد التقنية والمادية الكافية بما يتماشى واحتياجات الرابطة. Studysummary: The study aimed to identify the most important obstacles to digital transformation in the State Association for School Sports in the state of El Oued. To do this, we employed the descriptive analytical approach to suit the nature of the subject. The student used a questionnaire that was distributed to a sample of 40 administrators in the association. The data was processed statistically using the spss22 program. We concluded that there is There are human obstacles and organizational and administrative obstacles to a large degree, while there are material and technical obstacles to a moderate degree. There are also no statistically significant differences in the association’s members’ view of these obstacles due to the variables of professional experience and academic qualifications. Accordingly, we recommended the need to pay attention to employing competent human resources in managing associations and providing resources. Sufficient technical and material resources in line with the needs of the association. Résumé de l'étude L'étude visait à identifier les obstacles les plus importants à la transformation numérique au sein de l'Association nationale du sport scolaire de l'État d'El Oued. Pour ce faire, nous avons utilisé une approche analytique descriptive adaptée à la nature du sujet. a été distribuée à un échantillon de 40 administrateurs de l'association. Les données ont été traitées statistiquement à l'aide du programme spss22. Nous avons conclu qu'il existe des obstacles humains et des obstacles organisationnels et administratifs dans une large mesure, alors qu'il existe des obstacles matériels et techniques. degré modéré. Il n'y a pas non plus de différences statistiquement significatives dans l'opinion des membres de l'association sur ces obstacles en raison des variables d'expérience professionnelle et de qualification académique. Par conséquent, nous avons recommandé la nécessité de prêter attention à l'emploi de ressources humaines compétentes dans la gestion et l'offre des associations.Des moyens techniques et matériels adéquats et en adéquation avec les besoins de l'Association.
Keywords: المعوقات; التحول الرقمي; الرابطة الولائية للرياضة المدرسية; obstacles; digital transformation; state association for school sports; transformation numérique; association étatique pour le sport scolaire